Integrating lean six sigma and high-performance organizations : - Devane, Tom (Pfeiffer, 2004)
A volume in the Collaborative Work Systems series, this book is designed to help leaders-- at all levels of an organization-- combine two powerful methods of improving organizational performance. It meets the need to integrate best practices in "hard" (technical) and "soft" (people) aspects of performance improvement to achieve sustainable performance improvement and instill an attitude of continuous improvement in all members of an organization, not just a select few on a project improvement team.